Serial Vaccination and the Antigenic Distance Hypothesis: Effects on Influenza Vaccine Effectiveness During A(H3N2) Epidemics in Canada, 2010–2011 to 2014–2015. (9th February 2017) - Skowronski, Danuta M.; Chambers, Catharine; De Serres, Gaston; Sabaiduc, Suzana; Winter, Anne-Luise; Dickinson, James A.; Gubbay, Jonathan B.; Fonseca, Kevin; Drews, Steven J.; Charest, Hugues; Martineau, Christine; Krajden, Mel; et al.
Abstract: Background: The antigenic distance hypothesis (ADH) predicts that negative interference from prior season's influenza vaccine ( v1 ) on the current season's vaccine ( v2 ) protection may occur when the antigenic distance is small between v1 and v2 ( v1 ≈ v2 ) but large between v1 and the current epidemic ( e ) strain ( v1 ≠ e ). Methods: Vaccine effectiveness (VE) against medically attended, laboratory-confirmed influenza A(H3N2) illness was estimated by test-negative design during 3 A(H3N2) epidemics (2010–2011, 2012–2013, 2014–2015) in Canada. Vaccine effectiveness was derived with covariate adjustment across v2 and/or v1 categories relative to no vaccine receipt among outpatients aged ≥9 years. Prior vaccination effects were interpreted within the ADH framework. Results: Prior vaccination effects varied significantly by season, consistent with the ADH. There was no interference by v1 in 2010–2011 when v1 ≠ v2 and v1 ≠ e, with comparable VE for v2 alone or v2 + v1 : 34% (95% confidence interval [CI] = −51% to 71%) versus 34% (95% CI = −5% to 58%). Negative interference by v1 was suggested in 2012–2013 with nonsignificant reduction in VE when v1 ≈ v2 and v1 ≠ e : 49% (95% CI = −47% to 83%) versus 28% (95% CI = −12% to 54%). Negative effects of prior vaccination were pronounced and statistically significant in 2014–2015 when v1 ≡ v2 and v1 ≠ e : 65% (95% CI = 25% to 83%) versus −33% (95% CI = −78% to 1%). Conclusions: Effects of repeat influenza vaccination were consistent with the ADH and may have contributed to findings of low VE across recent A(H3N2) epidemics since 2010 in Canada.